Effectiveness of Wordwall as an Interactive Digital Tool for Teaching Vocabulary to Enhance Writing Skills of First Year Students - Puspitasari, Rina Puspitasari; Wahyu Satya Gumelar; M Andriana Gaffar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study evaluates the effectiveness of Wordwall, a gamified digital platform for vocabulary learning, in improving vocabulary mastery and procedural-writing quality among first-year vocational students in a Karawitan (traditional arts) program. Using a quasi-experimental pre-test–post-test design, two intact classes received different instructional treatments across three meetings held over a two-week period, the experimental class completed Wordwall activities, whereas the control class followed conventional methods. After initial differences were controlled with ANCOVA, the experimental class showed a significantly larger vocabulary gain (partial η² = 0.25) and greater improvements in lexical variety and technical accuracy in writing than the control class. These findings indicate that integrating Wordwall boosts student engagement and successfully transfers technical vocabulary to procedural texts. Therefore, teachers can adopt vocationally themed Wordwall tasks to accelerate language learning, and policy-makers should provide training and digital infrastructure so that interactive tools like Wordwall can be implemented widely in vocational schools.